2004
DOI: 10.1021/bi035726x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Semiquinone at the QB Site by A- or B-Branch Electron Transfer in the Reaction Center from Rhodobacter sphaeroides

Abstract: In Rhodobacter sphaeroides reaction centers containing the mutation Ala M260 to Trp (AM260W), transmembrane electron transfer along the A-branch of cofactors is prevented by the loss of the QA ubiquinone. Reaction centers that contain this AM260W mutation are proposed to photoaccumulate the P(+)QB- radical pair following transmembrane electron transfer along the B-branch of cofactors (Wakeham, M. C., Goodwin, M. G., McKibbin, C., and Jones, M. R. (2003) Photoaccumulation of the P(+)QB- radical pair state in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…Below we discuss the rationale for assigning the different conformational states. (66). The larger value of ~30% reported in this work is the hypothetical maximum fraction observed only at infinite light intensity.…”
Section: Molecular Basis For the Heterogeneity At The Quinone (Q B ) contrasting
confidence: 45%
“…Below we discuss the rationale for assigning the different conformational states. (66). The larger value of ~30% reported in this work is the hypothetical maximum fraction observed only at infinite light intensity.…”
Section: Molecular Basis For the Heterogeneity At The Quinone (Q B ) contrasting
confidence: 45%
“…Thus, the electron transfer within the iron-quinone complex and the OEC at the S 2 fi S 3 fi S 4 states is strongly influenced by configurations of proteins other than D1 and D2 and the electron flow within the edge domain on the acceptor and donor sides of PSII has a different character from the electron transfer TyrZ fi P680 fi Q A localized on the D1/D2 heterodimmer. This hypothesis is supported by the recent observation that the reduction of Q B by the B-branch pathway in purple bacterial reaction centers, where Q A ubiquinone is absent, still occurs at 100 K [112] whereas in the wild type of the bacterial reaction center, where the A-branch is active and Q B is reduced via Q A the temperature activation of fast collective fluctuations is necessary.…”
Section: Importance Of the Fast Collective Motions In Psiimentioning
confidence: 68%
“…However, the problem is more complicated because on the one hand surrounding polar groups may slow down the electron transfer due to their reorientation but on the other hand a polar environment also may positively influence the charge stabilization of the donor-acceptor pairs and may lower the activation and tunneling barriers increasing the driving force and the transfer rate [54]. Recently, also an activation of the second branch in PSI [46] and in bacterial reaction centers has been observed [40,64,75,112,113]. In view of these observations an intriguing question arises, whether such a bilateral activation of the acceptor side of PSI and such a branched electron transfer within PSII may occur in native systems.…”
Section: Electron Transfer and Arrangement Of Redox Active Cofactors mentioning
confidence: 99%
“…This mutation has been used by a number of groups to shut off electron transfer from HA -to QA in order to study primary charge separation without formation of long-lived radical pairs [50], P + HA -recombination [51], and the activation of inactive branch electron transfer [52][53][54][55]. In a recent report employing conductive atomic force microscopy on an orientated RC monolayer [13] it was shown that this mutation abolishes electron conduction across the RC under an applied bias, revealing that the strong functional asymmetry displayed by natural charge separation is retained when the RC is incorporated into an electrical circuit.…”
Section: Discussionmentioning
confidence: 99%